Developing a Multi-Joint Upper Limb Exoskeleton Robot for Diagnosis, Therapy, and Outcome Evaluation in Neurorehabilitation - Ren, Yupeng; Kang, Sang Hoon; Park, Hyung-Soon; Wu, Yi-Ning; Zhang, Li-Qun (IEEE transactions on neural systems and rehabilitation engineering, 2013)
Arm impairments in patients post stroke involve the shoulder, elbow and wrist simultaneously. It is not very clear how patients develop spasticity and reduced range of motion (ROM) at the multiple joints and the abnormal couplings among the multiple joints and the multiple degrees-of-freedom (DOF) during passive movement. It is also not clear how they lose independent control of individual joints/DOFs and coordination among the joints/DOFs during voluntary movement. An upper limb exoskeleton robot, the IntelliArm, which can control the shoulder, elbow, and wrist, was developed, aiming to support clinicians and patients with the following integrated capabilities: 1) quantitative, objective, and comprehensive multi-joint neuromechanical pre-evaluation capabilities aiding multi-joint/DOF diagnosis for individual patients; 2) strenuous and safe passive stretching of hypertonic/deformed arm for loosening up muscles/joints based on the robot-aided diagnosis; 3) (assistive/resistive) active reaching training after passive stretching for regaining/improving motor control ability; and 4) quantitative, objective, and comprehensive neuromechanical outcome evaluation at the level of individual joints/DOFs, multiple joints, and whole arm. Feasibility of the integrated capabilities was demonstrated through experiments with stroke survivors and healthy subjects.